A flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202311798589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-25
AI Technical Summary
[0004]针对现有技术中存在的问题,本发明提供一种柔性碳化Zn/Co-MOF@PDA@碳布光热复合材料及其制备方法和应用,从而解决现有技术中光热转换材料制备成本高以及稳定性差的技术问题
本发明公开一种柔性碳化Zn/Co-MOF@PDA@碳布光热复合材料的制备方法,首先将碳布置于含有多巴胺盐酸盐的Tris溶液中浸泡反应,制得聚多巴胺改性的碳布;然后将所述聚多巴胺改性的碳布置于六水合硝酸锌、六水合硝酸钴与2-甲基咪唑的混合水溶液中反应,制得表面生长有Zn/Co-MOF的聚多巴胺改性碳布;,随后通过惰性气氛下高温碳化,制得表面具有丰富层级结构的柔性碳化 Zn/Co-MOF@PDA@碳布材料,即最后对所述表面生长有Zn/Co-MOF的聚多巴胺改性碳布进行碳化处理,制得所述柔性碳化Zn/Co-MOF@PDA@碳布光热复合材料。本发明中的MOF基光热转换材料,其基底为碳布,其中碳布本身具有良好的宽频带吸光性和良好的耐腐蚀性,在碳布上生长Zn/Co-MOF,形成了金属骨架;聚多巴胺是一种生物黏结剂,利用聚多巴胺修饰基底可有效增加Zn/Co-MOF与基底之间的结合力,且修饰手段操作简单,条件温和环保,有利于制备与基底紧密链接的Zn/Co-MOF;碳化Zn/Co-MOF后形成的多孔碳在紫外-可见-近红外光范围具有良好的光吸收能力,因此在三者的协同下,实现了全太阳光谱的高效光吸收。此外,相较于相对光滑的碳布(CF)表面,碳化Zn/Co-MOF后形成的多孔碳,不仅会产生毛细作用,促进蒸发过程中充足水供给,而且丰富的孔径和大的比表面积,提供了丰富的蒸发位点。依靠毛细作用力产生的超亲水特性,在快速水供给的同时,可以实现高浓度盐水的回流和扩散,提高了柔性碳化Zn/Co-MOF@PDA@碳布光热材料在海水淡化应用过程中的耐盐性和长期使用性能稳定性。碳布具有极好的柔性,获得的柔性碳化Zn/Co-MOF@PDA@碳布光热材料同样具有极好的柔性,因此材料的结构稳定性和区域间的运输能力强。本发明得到的柔性碳化Zn/Co-MOF@PDA@碳布光热材料,用于高效的界面太阳能水蒸发,由于其表面生长的金属骨架碳化后形成的多孔结构,增加了光吸收能力,拥有良好的光热转化和水运输能力,极大的提高了海水蒸发和淡化的效率,本发明公开的制备方法,具有操作简单,对于缓解淡水资源短缺具有重要的意义。
Smart Images

Figure CN117779470B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photothermal material development technology, and relates to a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material, its preparation method and application. Background Technology
[0002] Freshwater scarcity has always been a major challenge facing humanity. Although the total amount of water resources on Earth is vast, less than 3% is freshwater, and most of this freshwater faces difficulties in extraction and severe pollution, posing a serious constraint and threat to human progress and development. Currently, one of the recognized effective solutions to the freshwater crisis is seawater desalination technology. Traditional seawater desalination technologies often directly or indirectly consume non-renewable fossil fuels. While this can alleviate the freshwater crisis to some extent, it also brings problems such as environmental pollution and the greenhouse effect. Solar energy, as a green, clean, abundant, and renewable energy source, has great potential in replacing fossil fuels. Therefore, utilizing solar energy to convert into heat energy for water evaporation can effectively avoid environmental pollution and the greenhouse effect, making it a very effective and feasible technology for seawater desalination. In recent years, interfacial solar steam generation has been considered a promising seawater desalination technology, thus photothermal conversion materials have received considerable attention.
[0003] Existing photothermal conversion materials mainly include carbon-based materials, plasma-enhanced metal nanoparticles, biomass materials, and semiconductor materials. Plasma-enhanced metal nanoparticles possess excellent photothermal conversion performance, but their high preparation cost limits their large-scale application. Biomass materials, after high-temperature carbonization, inherently exhibit brittleness, which hinders transportation and installation, affecting long-term stability. Semiconductor materials are expensive to prepare, some are difficult to mass-produce, and may experience stability issues during long-term service, thus limiting their practical application in seawater desalination. Summary of the Invention
[0004] To address the problems existing in the prior art, this invention provides a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material, its preparation method, and its application, thereby solving the technical problems of high preparation cost and poor stability of photothermal conversion materials in the prior art.
[0005] This invention is achieved through the following technical solution: A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: S1: Carbon cloth was immersed in a Tris solution containing dopamine hydrochloride to prepare polydopamine-modified carbon cloth. S2: The polydopamine-modified carbon fabric is reacted in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate and 2-methylimidazole to obtain a polydopamine-modified carbon cloth with Zn / Co-MOF growing on its surface. S3: Carbonize the polydopamine-modified carbon cloth with Zn / Co-MOF grown on its surface to obtain the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material.
[0006] Preferably, in step S1, before reacting the carbon cloth in a Tris solution containing dopamine hydrochloride, the carbon cloth is pretreated, the pretreatment including: S11: The carbon cloth is ultrasonically treated in acetone, ethanol, and water in sequence, and then dried; S12: The carbon from step S11 is placed in concentrated nitric acid, reacted in a water bath, and then washed and dried to complete the pretreatment process.
[0007] Preferably, in step S12, the reaction temperature of the water bath reaction is 80~90℃, and the reaction time is 4~5h.
[0008] Preferably, in the Tris solution containing dopamine hydrochloride, the ratio of dopamine hydrochloride to Tris solution is (1-3) mg:(0.5-1.5) mL.
[0009] Preferably, the carbon cloth is soaked in a Tris solution containing dopamine hydrochloride for 4-5 hours.
[0010] Preferably, in step S2, the mass ratio of zinc nitrate hexahydrate, cobalt nitrate hexahydrate and 2-methylimidazole is (0.5-2):(1-3):(5-8).
[0011] Preferably, in step S2, the reaction of the polydopamine-modified carbon in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate and 2-methylimidazole is specifically as follows: first, the polydopamine-modified carbon is arranged in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate and 2-methylimidazole and grown under ultrasonic assistance for 1 min, and then placed at room temperature for 4-5 h for reaction growth.
[0012] Preferably, in step S3, the carbonization temperature is 500~700℃ and the carbonization time is 2-3h.
[0013] A flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material was prepared by the above method.
[0014] The above-mentioned flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material is applied in the field of interfacial solar water evaporation.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material. First, carbon cloth is immersed in a Tris solution containing dopamine hydrochloride to obtain polydopamine-modified carbon cloth. Then, the polydopamine-modified carbon cloth is reacted in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole to obtain polydopamine-modified carbon cloth with Zn / Co-MOF grown on its surface. Subsequently, high-temperature carbonization under an inert atmosphere yields a flexible carbonized Zn / Co-MOF@PDA@carbon cloth material with a rich hierarchical structure on its surface. Finally, the polydopamine-modified carbon cloth with Zn / Co-MOF grown on its surface is subjected to carbonization treatment to obtain the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material. The MOF-based photothermal conversion material of this invention uses carbon cloth as its substrate. Carbon cloth itself possesses excellent broadband light absorption and corrosion resistance. Zn / Co-MOF is grown on the carbon cloth, forming a metallic framework. Polydopamine, a bio-adhesive, effectively increases the bonding force between Zn / Co-MOF and the substrate by modifying the substrate. Furthermore, the modification method is simple, mild, and environmentally friendly, facilitating the preparation of Zn / Co-MOF tightly bonded to the substrate. The porous carbon formed after carbonizing Zn / Co-MOF exhibits excellent light absorption in the ultraviolet-visible-near-infrared range. Therefore, through the synergy of these three factors, efficient light absorption across the entire solar spectrum is achieved. Moreover, compared to the relatively smooth surface of carbon cloth (CF), the porous carbon formed after carbonizing Zn / Co-MOF not only generates capillary action, promoting sufficient water supply during evaporation, but also provides abundant evaporation sites due to its rich pore size and large specific surface area. Relying on the superhydrophilic properties generated by capillary forces, high-concentration brine reflux and diffusion can be achieved simultaneously with rapid water supply, improving the salt resistance and long-term performance stability of the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal material in seawater desalination applications. Carbon cloth possesses excellent flexibility, and the resulting flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal material also exhibits excellent flexibility, thus demonstrating strong structural stability and inter-regional transport capabilities. The flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal material obtained in this invention is used for efficient interfacial solar water evaporation. Due to the porous structure formed by the carbonization of the metal skeleton grown on its surface, light absorption capacity is increased, resulting in excellent photothermal conversion and water transport capabilities, greatly improving the efficiency of seawater evaporation and desalination. The preparation method disclosed in this invention is simple to operate and has significant implications for alleviating freshwater resource shortages.
[0016] Furthermore, in step S1, before reacting the carbon fabric in a Tris solution containing dopamine hydrochloride, the carbon fabric is pretreated. This pretreatment includes sequentially ultrasonicating the carbon fabric with acetone, ethanol, and water, followed by drying. This process effectively removes contaminants present on the surface of the carbon fabric. Then, the dried carbon fabric is reacted in concentrated nitric acid in a water bath, followed by washing and drying to complete the pretreatment process. This process results in oxygen-containing functional groups on the surface of the carbon fabric, providing reaction and binding sites for subsequent material preparation.
[0017] Furthermore, the dried carbon cloth is placed in a concentrated nitric acid bath for a water bath reaction at a temperature of 80-90°C for 4-5 hours, followed by washing and drying to complete the pretreatment process. This process allows oxygen-containing functional groups to be present on the surface of the carbon cloth, providing reaction and binding sites for subsequent material preparation.
[0018] Furthermore, in the Tris solution containing dopamine hydrochloride, the ratio of dopamine hydrochloride to Tris solution is (1-3) mg:(0.5-1.5) mL, which allows dopamine hydrochloride to be completely dissolved in the Tris solution to form polydopamine (PDA).
[0019] Furthermore, the carbon cloth is soaked in a Tris solution containing dopamine hydrochloride for 4-5 hours, which allows the PDA to be completely coated on the surface of the carbon cloth.
[0020] Furthermore, in step S2, the mass ratio of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole is (0.5-2):(1-3):(5-8), which allows Zn / Co-MOF to form.
[0021] Furthermore, in step S2, the reaction of the polydopamine-modified carbon in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole is specifically as follows: First, the polydopamine-modified carbon is ultrasonically assisted to grow for 1 minute in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole, and then placed at room temperature for 4-5 hours to grow. This process allows the Zn / Co-MOF to be more uniformly and completely coated on the surface of the carbon cloth coated with PDA.
[0022] Furthermore, in step S3, during the carbonization process, the carbonization temperature is 500~700℃, the carbonization time is 500~700℃, and the carbonization time is 2-3 hours, which allows Zn / Co-MOF to be completely converted into porous carbon. Attached Figure Description To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the process for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material according to the present invention; Figure 2 The figures are contact angle test diagrams, where (a) is the original carbon cloth contact angle test diagram and (b) is the CZCPF contact angle test diagram in Embodiment 2 of the invention. Figure 3 The images are SEM images, where (a), (b), and (c) are SEM images of the original carbon cloth, and (d), (e), and (f) are SEM images of CZCPF after carbonization at 600°C in Example 2. Figure 4 This is a CZCPF flexibility test diagram as described in this invention; Figure 5 The light absorption capacity test diagrams of the CZCPF and the original carbon cloth sample described in this invention are shown. Figure 6 (a) and (b) are respectively the mass change curves and evaporation rate change graphs of the CZCPF sample and the original carbon cloth described in this invention, which are placed in 3.5wt% sea salt water and evaporated water under 1 light intensity. Figure 7 The surface temperature change curves of the CZCPF and the original carbon cloth sample (in a dry state) under one sun during the switching on and off of the light. Detailed Implementation
[0024] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0026] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0027] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0028] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0029] like Figure 1 As shown, this invention provides a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal material and its preparation method, comprising the following steps: The original carbon cloth sample was cleaned in a CNC ultrasonic cleaner with a frequency of 30-50kHz by sequentially washing it with acetone, anhydrous ethanol, and deionized water for 20 minutes each. Then, it was placed in a disposable petri dish and dried at room temperature for 5 hours to obtain clean carbon cloth. The carbon cloth was then placed in concentrated nitric acid and reacted in a water bath at 80℃-90℃ for 4-5 hours. After washing with deionized water until neutral, it was placed in a disposable petri dish and dried at room temperature for 24 hours to obtain dry carbon cloth.
[0030] PDA was grown on a carbon cloth substrate by placing the carbon cloth in a Tris solution containing dopamine hydrochloride and reacting for 4-5 hours to obtain PDA@carbon cloth; the mixing ratio of dopamine hydrochloride to Tris solution was 2 mg: 1 mL; the PDA@carbon cloth was placed in a disposable petri dish and dried at room temperature for 12 hours to obtain dried PDA carbon cloth.
[0031] To grow Zn / Co-MOF on PDA@carbon cloth, zinc nitrate hexahydrate and cobalt nitrate hexahydrate were dissolved in deionized water at a ratio of 5 mg:10 mg:1 mL; 2-methylimidazole was dissolved in deionized water at a ratio of 35 mg:1 mL; the mass ratio of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole was 1:2:7. The resulting metal salt solution and 2-methylimidazole solution were rapidly mixed to obtain the reaction solution. PDA@carbon cloth was placed in the reaction solution and grown at room temperature for 5 h. After washing several times with deionized water, it was placed in a disposable petri dish and dried.
[0032] The flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material is prepared by carbonizing Zn / Co-MOF@PDA@carbon cloth in a tube furnace.
[0033] II. Solar Steam Experiment A 3.5 wt% seawater solution was prepared to simulate seawater concentration, and a xenon lamp (CEL-S500, AM1.5 filter) was used to simulate solar light. The evaporation process was monitored using an electronic balance (AR224CN) with an accuracy of 0.0001 g, and the data was transmitted and recorded to a personal computer (PC) via SPDC data acquisition software V2.01. A simulated solar evaporation experimental platform was constructed. Analysis and calculations revealed the simulated seawater evaporation rate and the photothermal conversion efficiency of the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material under experimental conditions, and the photothermal performance was studied.
[0034] The beaker was placed inside a protective sleeve of polyvinyl chloride (PVC) foam to minimize the impact of ambient temperature changes during the experiment. Then, the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material was placed on PVC foam wrapped in a superhydrophilic cleanroom cloth, ensuring stable floating in 3.5 wt% simulated seawater. All evaporation devices were placed on a precision electronic balance to monitor mass changes due to water evaporation in real time. Under one sun (1 kW m³), the experiment was conducted... -2 ), to conduct solar steam generation tests.
[0035] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0036] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0037] Example 1 A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: Step 1: Clean the original carbon cloth (3cm×3cm) with acetone, anhydrous ethanol and deionized water in sequence for 20 minutes by ultrasonic cleaning, and then let it dry for later use; place the dried carbon cloth in concentrated nitric acid and react in a water bath at 80℃ for 4 hours, then wash it with deionized water until neutral and dry it for later use. Step 2: Weigh 50g of dopamine hydrochloride using an electronic balance and dissolve it in 25mL of prepared Tris solution; place the dried carbon array in the salt dopamine solution and grow at room temperature for 24h, then wash with deionized water and dry. Step 3: Weigh 0.1863g of zinc nitrate hexahydrate and 0.5889g of cobalt nitrate hexahydrate using an electronic balance, and then dissolve them in 40mL of deionized water to obtain a homogeneous metal salt solution; weigh 1.3134g of 2-methylimidazole using an electronic balance, and dissolve it in 40mL of deionized water to obtain a homogeneous 2-methylimidazole solution; quickly pour the 2-methylimidazole solution into the metal salt solution, mix well, and obtain the reaction solution; Step 4: Place the dried carbon in the reaction solution, grow at room temperature for 5 hours, wash several times with deionized water, and then dry for later use. Step 5: Arrange the dried and prepared carbon in a tube furnace for carbonization at a temperature of 500℃ for 2 hours.
[0038] Example 2 A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: Step 1: Clean the original carbon cloth (4cm×4cm) with acetone, anhydrous ethanol and deionized water in sequence by ultrasonic cleaning for 20min and then let it dry for later use; place the dried carbon cloth in concentrated nitric acid and react in a water bath at 85℃ for 4.5h, then wash with deionized water until neutral and dry for later use. Step 2: Weigh 30g of dopamine hydrochloride using an electronic balance and dissolve it in 20mL of prepared Tris solution; place the dried carbon array in the dopamine hydrochloride solution and grow at room temperature for 24 hours, then wash with deionized water and dry. Step 3: Weigh 0.1863g of zinc nitrate hexahydrate and 0.3880g of cobalt nitrate hexahydrate using an electronic balance, and then dissolve them in 40mL of deionized water to obtain a homogeneous metal salt solution; weigh 1.3134g of 2-methylimidazole using an electronic balance, and dissolve it in 50mL of deionized water to obtain a homogeneous 2-methylimidazole solution; quickly pour the 2-methylimidazole solution into the metal salt solution, mix well, and obtain the reaction solution; Step 4: Place the dried carbon in the reaction solution, grow at room temperature for 5 hours, wash several times with deionized water, and then dry for later use. Step 5: Arrange the dried and prepared carbon in a tube furnace for carbonization at a temperature of 600℃ for 2 hours.
[0039] Example 3 A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: Step 1: Clean the original carbon cloth (2cm×5cm) with acetone, anhydrous ethanol and deionized water in sequence for 20min, and then let it dry for later use; place the dried carbon cloth in concentrated nitric acid and react in a water bath at 90℃ for 4h, then wash it with deionized water until neutral and dry it for later use. Step 2: Weigh 37.5g of dopamine hydrochloride using an electronic balance and dissolve it in 25mL of prepared Tris solution; place the dried carbon array in the dopamine hydrochloride solution and grow at room temperature for 24h, then wash with deionized water and dry. Step 3: Weigh 0.1863g of zinc nitrate hexahydrate and 0.5589g of cobalt nitrate hexahydrate using an electronic balance, and then dissolve them in 50mL of deionized water to obtain a homogeneous metal salt solution; weigh 1.3041g of 2-methylimidazole using an electronic balance, and dissolve it in 50mL of deionized water to obtain a homogeneous 2-methylimidazole solution; quickly pour the 2-methylimidazole solution into the metal salt solution, mix well, and obtain the reaction solution; Step 4: Arrange the dried carbon in the reaction solution, grow it with ultrasound assistance for 1 minute, then grow it at room temperature for 5 hours. Wash it several times with deionized water and then dry it for later use. Step 5: Arrange the dried and prepared carbon in a tube furnace for carbonization at a temperature of 700℃ for 2 hours.
[0040] Example 4 A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: Step 1: Clean the original carbon cloth (2.5cm×4cm) with acetone, anhydrous ethanol and deionized water in sequence for 20min by ultrasonic cleaning, and then let it dry for later use; place the dried carbon cloth in concentrated nitric acid and react in a water bath at 80℃ for 5h, then wash with deionized water until neutral and dry for later use. Step 2: Weigh 50 mg of dopamine hydrochloride using an electronic balance and dissolve it in 25 mL of prepared Tris solution; place the dried carbon array in the salt dopamine solution and grow at room temperature for 24 h, then wash with deionized water and dry. Step 3: Weigh 0.1863g of zinc nitrate hexahydrate and 0.3880g of cobalt nitrate hexahydrate using an electronic balance, and then dissolve them in 40mL of deionized water to obtain a homogeneous metal salt solution; weigh 1.3134g of 2-methylimidazole using an electronic balance, and dissolve it in 40mL of deionized water to obtain a homogeneous 2-methylimidazole solution; quickly pour the 2-methylimidazole solution into the metal salt solution, mix well, and obtain the reaction solution; Step 4: Arrange the dried carbon in the reaction solution, grow at room temperature for 5 hours, wash several times with deionized water, and then dry for later use. Step 5: Arrange the dried and prepared carbon in a tube furnace for carbonization at a temperature of 600℃ for 2.5 hours.
[0041] Example 5 A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: Step 1: Clean the original carbon cloth (3cm×3cm) with acetone, anhydrous ethanol and deionized water in sequence for 20 minutes by ultrasonic cleaning, and then let it dry for later use; place the dried carbon cloth in concentrated nitric acid and react in a water bath at 80℃ for 4 hours, then wash it with deionized water until neutral and dry it for later use. Step 2: Weigh 12.5 mg of dopamine hydrochloride using an electronic balance and dissolve it in 25 mL of prepared Tris solution; place the dried carbon array in the dopamine hydrochloride solution and grow at room temperature for 24 h, then wash with deionized water and dry. Step 3: Weigh 0.1863g of zinc nitrate hexahydrate and 0.3726g of cobalt nitrate hexahydrate using an electronic balance, and then dissolve them in 50mL of deionized water to obtain a homogeneous metal salt solution; weigh 1.1178g of 2-methylimidazole using an electronic balance, and dissolve it in 60mL of deionized water to obtain a homogeneous 2-methylimidazole solution; quickly pour the 2-methylimidazole solution into the metal salt solution, mix well, and obtain the reaction solution; Step 4: Arrange the dried carbon in the reaction solution, grow at room temperature for 4.5 hours, wash several times with deionized water, and then dry for later use. Step 5: Arrange the dried and prepared carbon in a tube furnace for carbonization at a temperature of 600℃ for 3 hours.
[0042] Example 6 A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material includes the following steps: Step 1: Clean the original carbon cloth (3cm×3cm) with acetone, anhydrous ethanol and deionized water in sequence for 20 minutes by ultrasonic cleaning, and then let it dry for later use; place the dried carbon cloth in concentrated nitric acid and react in a water bath at 80℃ for 4 hours, then wash it with deionized water until neutral and dry it for later use. Step 2: Weigh 50 mg of dopamine hydrochloride using an electronic balance and dissolve it in 25 mL of prepared Tris solution; place the dried carbon array in the salt dopamine solution and grow at room temperature for 24 h, then wash with deionized water and dry. Step 3: Weigh 0.1940g of zinc nitrate hexahydrate and 0.3880g of cobalt nitrate hexahydrate using an electronic balance, and then dissolve them in 50mL of deionized water to obtain a homogeneous metal salt solution; weigh 1.9400g of 2-methylimidazole using an electronic balance, and dissolve it in 50mL of deionized water to obtain a homogeneous 2-methylimidazole solution; quickly pour the 2-methylimidazole solution into the metal salt solution, mix well, and obtain the reaction solution; Step 4: Arrange the dried carbon in the reaction solution, grow at room temperature for 4 hours, wash several times with deionized water, and then dry for later use. Step 5: Arrange the dried and prepared carbon in a tube furnace for carbonization at a temperature of 600℃ for 2 hours.
[0043] The present invention will now be described in further detail with reference to the accompanying drawings: I. Contact Angle Test Figure 2 The figures are contact angle test diagrams, where (a) is the original carbon cloth contact angle test diagram, and (b) is the CZCPF contact angle test diagram in Embodiment 2 of the invention; from Figure 2 (b) clearly shows that the water droplet was completely absorbed by CZCPF in 0.01s, which indicates that CZCPF has excellent superhydrophilic properties.
[0044] II. SEM Image Testing Figure 3 The images are SEM images, where (a), (b), and (c) are the original carbon cloth, and (d), (e), and (f) are CZCPF carbonized at 600°C in Example 2. Figure 3 (d)(e)(f) indicates that the CZCPF surface has abundant pores and nanoplate array structure.
[0045] III. Flexibility Test Figure 4 The figure shows the CZCPF flexibility test results in Example 2. As can be seen from the figure, the CZCPF can still recover to its original shape after bending, indicating that the CZCPF prepared by the technical solution of the present invention has good flexibility.
[0046] IV. Full Solar Spectrum Light Absorption Capacity Test Figure 5 The image shows the spectral absorption of the original carbon cloth and CZCPF under AM1.5 sunlight. It can be seen from the image that the original carbon cloth has 80% light absorption in the 200-2500nm spectral range, while CZCPF has 90% light absorption.
[0047] V. Solar Steam Experiment The evaporation performance of CZCPF is tested through quantitative analysis using evaporation experiments: Figure 6(a) and (b) are respectively the mass change curves and evaporation rate change graphs of the CZCPF sample and the original carbon cloth described in this invention, which are placed in 3.5wt% sea salt water and evaporated water under 1 light intensity. The evaporation experiments were conducted using an experimental setup simulating sunlight. All data was read via an electronic balance using the mass difference of the brine and then transmitted to a computer for recording. All evaporation experiments were performed under a single solar radiation intensity.
[0048] Evaporation experiments revealed that the mass of the simulated seawater evaporated increased continuously over time as evaporation proceeded, and the mass change tended to stabilize. Furthermore, compared to the original carbon cloth, the CZCPF prepared in Example 2 exhibited an evaporation rate of 1.83 kg·m³. -2 ·h -1 The original carbon cloth only weighed 1.42 kg·m³. -2 ·h -1 Clearly, growing PDA on CF substrate and then growing Zn / Co-MOF on the surface and carbonizing it as a photothermal material greatly improves the efficiency of solar-driven interface water evaporation.
[0049] VI. Photothermal Response Speed Test Figure 7 The surface temperature change curves of the CZCPF and the original carbon cloth sample (in a dry state) under one sun during the switching on and off of the light.
[0050] The CZCPF prepared in Example 2 of this invention has excellent photothermal response capability. It can reach a stable temperature of 95.11°C within 180 seconds under one sun. Under no light conditions, the surface temperature drops rapidly to room temperature, while the original CF can only rise to 81.64°C under the same conditions.
[0051] In summary, this invention provides a method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material and its application in interfacial solar seawater evaporation. Utilizing a layered porous structure, it exhibits excellent light absorption and photothermal conversion capabilities. Simultaneously, the capillary forces generated by the formed pores endow the composite photothermal material with excellent superhydrophilicity, resulting in an ultra-high evaporation rate. Furthermore, the carbon cloth possesses excellent flexibility, and materials prepared using carbon cloth as a substrate exhibit structural stability and portability. Overall, this invention provides a novel photothermal conversion material for solar-driven seawater desalination technology.
[0052] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material, characterized in that, Includes the following steps: S1: Carbon cloth was immersed in a Tris solution containing dopamine hydrochloride to prepare polydopamine-modified carbon cloth. S2: The polydopamine-modified carbon fabric is reacted in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate and 2-methylimidazole to obtain a polydopamine-modified carbon cloth with Zn / Co-MOF growing on its surface. S3: Carbonize the polydopamine-modified carbon cloth with Zn / Co-MOF grown on its surface to obtain the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material. In step S2, the mass ratio of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole is (0.5-2):(1-3):(5-8); In step S2, the polydopamine-modified carbon is first placed in a mixed aqueous solution of zinc nitrate hexahydrate, cobalt nitrate hexahydrate and 2-methylimidazole and grown under ultrasonic assistance for 1 min, and then placed at room temperature for 4-5 h to grow. In step S1, before reacting the carbon cloth in a Tris solution containing dopamine hydrochloride, the carbon cloth is pretreated, the pretreatment including: S11: The carbon cloth is ultrasonically treated in acetone, ethanol, and water in sequence, and then dried; S12: The carbon from step S11 is placed in concentrated nitric acid, reacted in a water bath, and then washed and dried to complete the pretreatment process. In step S12, the reaction temperature of the water bath reaction is 80~90℃, and the reaction time is 4~5h; The carbon cloth is soaked in a Tris solution containing dopamine hydrochloride for 4-5 hours. In step S3, the carbonization process is carried out in an inert atmosphere, the carbonization temperature is 500~700℃, and the carbonization time is 2-3h.
2. The method for preparing a flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material according to claim 1, characterized in that, In the Tris solution containing dopamine hydrochloride, the ratio of dopamine hydrochloride to Tris solution is (1-3) mg:(0.5-1.5) mL.
3. A flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material, characterized in that, It is prepared by the method described in any one of claims 1 to 2.
4. The application of the flexible carbonized Zn / Co-MOF@PDA@carbon cloth photothermal composite material as described in claim 3 in the field of interfacial solar water evaporation.
Citation Information
Patent Citations
Rigid-flexible ZIF-8 / dopamine synergistically enhanced paper-based friction material and preparation method thereof
CN113445360A
Method for treating organic sewage by utilizing solar photo-thermal catalysis
CN115159606A